Warren Buffett and the Interpretation of Financial Statements - Buffett, Mary; Clark, David (Tantor Media, Inc., 2008)
Mary Buffett and David Clark clearly outline Warren Buffett's strategies in a way that will appeal to newcomers and seasoned Buffettologists alike. Inspired by the seminal work of Buffett's mentor, Benjamin Graham (The Interpretation of Financial Statements, 1937), this book presents Buffett's interpretation of financial statements with anecdotes and quotes from the master investor himself. Potential investors will discover: -Buffett's time-tested dos and don'ts for interpreting an income statement and balance sheet -Why high research and development costs can kill a great business -How much debt Buffett thinks a company can carry before it becomes too dangerous to touch -The financial ratios and calculations that Buffett uses to identify the company with a durable competitive advantage-which he believes makes for the winning long-term investment -How Buffett uses financial statements to value a company -What kinds of companies Warren stays away from no matter how cheap their selling price Once audiences complete and master Buffett's simple financial calculations and methods for interpreting a company's financial statement, they will be well on their way to identifying which companies are going to be tomorrow's winners-and which will be the losers that should be avoided at all costs. Destined to become a classic in the world of investment books, Warren Buffett and the Interpretation of Financial Statements is the perfect companion volume to The New Buffettology and The Tao of Warren Buffett.
Online resource; Title from title page (viewed December 8, 2008)
Keywords: Buffett, Warren; Financial statements; Business enterprises -- Finance; Corporations -- Finance; Investment analysis; Investments -- Decision making; Analyse financière; Investissements; Prise de décision; Business enterprises; Finance; Corporations; Finance; Investments; Decision making; Downloadable audio books; Audiobooks; Livres audio